2019
DOI: 10.3390/ijerph16122201
|View full text |Cite
|
Sign up to set email alerts
|

Gender Division of Labor, Burnout, and Intention to Leave Work Among Young Female Nurses in Japan: A Cross-Sectional Study

Abstract: Women in Japan face difficulties balancing work and personal life due to the gender division of labor, and medical professions are no exception. The purpose of this study was to investigate if the gender division of labor affects the intention to leave the workplace among the nursing profession. Among 328 female nurses working for three university-affiliated hospitals in Tokyo, Japan, above 70% were in their 20s and 30s and single, and agreed with the gender division of labor that men should be the breadwinner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 39 publications
5
33
4
1
Order By: Relevance
“…In addition, number of children, years of working, PJ fit, and support from outside the family were associated with specific dimensions of turnover intention. These results too are consistent with previous findings (Chang, Chu, Liao, Chang, & Teng, 2019; Han, Kim, Lee, & Lim, 2019; Minamizono et al., 2019). With this information, nurse administrators should be better equipped to identify vulnerable staff (such as pregnant nurses) and to develop appropriate strategies (i.e., provision of professional psychosocial support and appropriate job type) to reduce the turnover rate among NGNs.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, number of children, years of working, PJ fit, and support from outside the family were associated with specific dimensions of turnover intention. These results too are consistent with previous findings (Chang, Chu, Liao, Chang, & Teng, 2019; Han, Kim, Lee, & Lim, 2019; Minamizono et al., 2019). With this information, nurse administrators should be better equipped to identify vulnerable staff (such as pregnant nurses) and to develop appropriate strategies (i.e., provision of professional psychosocial support and appropriate job type) to reduce the turnover rate among NGNs.…”
Section: Discussionsupporting
confidence: 93%
“…Supportive supervisors can help female nurses and physicians handle critical patients properly and effectively by providing personal coaching. These supervisors can also provide them with the confidence to achieve high-quality standards in their work across many different tasks [53,54]. Meanwhile, supportive colleagues can offer help to cover additional work when female nurses and physicians suffer from irregular and long working hours.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Therefore, the perceived social support of peers and superiors affects the healthcare resources of the healthcare professional, which, in turn, influences burnout levels [46]. Research has also indicated that good communication and relationships between team members and their superiors constitute a protective variable against burnout [47] and that having the support of colleagues with more experience reduces the intention to leave the job among the most inexperienced nurses [48].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the vulnerability to stress is a risk factor for developing burnout [59,60], and stress management has been established as one of the key variables in the design of interventions that aim to reduce the incidence of this syndrome [12]. Accordingly, Minamizono et al [48] reported that working conditions by themselves were not associated with the intention to leave the workplace among nursing professionals. This suggests that it is the low resistance to stress, especially prevalent among the youngest and most inexperienced professionals, that increases the intention to rotate.…”
Section: Introductionmentioning
confidence: 99%